Bioprospecção dos efeitos tóxicos, antibacterianos e antioxidantes da flavona e de seus derivados hidroxilados - Montenegro , Camila de Albuquerque (2015)
Phenolic compounds, among them the flavonoids, are holders of antimicrobial, antioxidant and anti-inflammatory effects, but not free from toxicity and/or adverse effects, that's why research in this area, whether they are in silico, in vitro and/or in vivo approach have been intensified to ensure the safe use of these molecules. Thus, the aim of this study was to investigate the probable pharmacological activities, toxicity and antibacterial and antioxidant effects of flavonoid flavone and its hydroxy derivatives: 3-hydroxyflavone, 5-hydroxyflavone and 6-hydroxyflavone, tracing a structure-activity relationship of such substances. It was investigated the pharmacological, pharmacokinetics and theoretical toxicological characteristics of flavonoids using in silico testing with the PASS online and Osiris softwares; the cytotoxicity on human erythrocytes of blood types A, B and O positive and negative Rh factor, running the models of hemolysis and Erythrocyte Osmotic Fragility (EOF); was analysed the antimicrobial activity in front of Gram-positive (B. subtilis CCT 0516, S. aureus ATCC 25619 and S. aureus ATCC 25925) and Gram-negative, including clinical importance (P. aeruginosa ATCC 8027, P. aeruginosa ATCC 23243, E. coli ATCC 2536, E. coli 101, E. coli 103, E. coli 104, E. coli 105 and E. coli 108); assessed the oxidant and antioxidant potential of these molecules in the presence of Reactive Oxygen Species (ROS - H2O2) and phenylhydrazinium (Ph) and, finally, the genotoxicity using the micronucleus test. The results obtained revealed numerous probable pharmacological activities to the flavonoids, as integrity agonists and membrane permeability inhibitors, anaphylatoxin receptor antagonists, inhibitors of kinase and peroxidase, antimutagenic potential and vase-protecting capacity; do not present significant theoretical toxicity risks and have good oral bioavailability. The 4 flavonoids have shown moderate hemolysis at concentrations of 500 and 1000 μg/mL, the example of 3-hydroxyflavone which induced 20.2 % and 53 % of hemolysis, respectively, in blood type A, Rh+; the flavonoids hydroxylated protected cells types A and O from osmotic stress. All flavonoids exhibited moderate antibacterial activity against Gram-positive strains and Gram-negative, being the flavone bactericide in the concentration of 200 μg/mL to the strains of P. aeruginosa ATCC 8027, S. aureus ATCC 25619 and E. coli 104, while other flavonoids have bacteriostatic action. It did not promote oxidation of erythrocyte and behaved as scavengers and antioxidants of H2O2 and phenylhydrazinium and finally the flavone did not show genotoxicity compared to cyclophosphamide, a proven genotoxic agent. It is concluded that the flavone, 3-hydroxyflavone, 5-hydroxyflavone and 6- hydroxyflavone have different pharmacological activities, good bioavailability and low theoreticals toxicity, reduced cytotoxicity, absence of genotoxicity as well as being moderate antibacterial and antioxidant, showing, with this study, the importance of the inclusion of computational chemistry techniques for targeting evaluation protocols of the biological effects of the molecules.